2019
DOI: 10.1371/journal.pbio.3000217
|View full text |Cite
|
Sign up to set email alerts
|

How host genetics dictates successful viral zoonosis

Abstract: Viruses of wild and domestic animals can infect humans in a process called zoonosis, and these events can give rise to explosive epidemics such as those caused by the HIV and Ebola viruses. While humans are constantly exposed to animal viruses, those that can successfully infect and transmit between humans are exceedingly rare. The key event in zoonosis is when an animal virus begins to replicate (one virion making many) in the first human subject. Only at this point will the animal virus first experience the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 115 publications
(146 reference statements)
2
66
0
Order By: Relevance
“…VACV K3 has well-defined species-specific differences in its ability to inhibit PKR across the mammalian phylogeny, defined by both LBR assays and yeast-based studies [8,9,17]. The data presented here support and extend this species-specific sensitivity of PKR to VACV K3L and add to a growing body of evidence that virus-specific differences play an important role in viral host range, as do species-specific differences in host genes [22,23]. Consistent with this concept, in this study we showed that the VACV K3 orthologs from four different orthopoxviruses display dramatic differences in their ability to inhibit PKR from different species, including different sensitivities in closely related species such as mice and rats.…”
Section: Discussionsupporting
confidence: 63%
“…VACV K3 has well-defined species-specific differences in its ability to inhibit PKR across the mammalian phylogeny, defined by both LBR assays and yeast-based studies [8,9,17]. The data presented here support and extend this species-specific sensitivity of PKR to VACV K3L and add to a growing body of evidence that virus-specific differences play an important role in viral host range, as do species-specific differences in host genes [22,23]. Consistent with this concept, in this study we showed that the VACV K3 orthologs from four different orthopoxviruses display dramatic differences in their ability to inhibit PKR from different species, including different sensitivities in closely related species such as mice and rats.…”
Section: Discussionsupporting
confidence: 63%
“…By 7 February, the number of cases had increased to 29, including individuals without travel history to China, prompting Singaporean authorities to implement control measures aimed at reducing the community spread of the virus ( 3 ). Successful zoonotic viral transmission from animals to humans is often associated with the ability of viruses to adapt to a new host, via genetic mutation events, and cause sustained transmission ( 4 6 ). A variety of genomic changes, including mutations, deletions, and recombinations, have been frequently observed in the other two documented zoonotic coronaviruses, SARS-CoV and Middle East respiratory syndrome-coronavirus (MERS-CoV) ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, viruses are usually well adapted to their host, and cross-species transmissions can be limited by host factor incompatibilities and restriction factors ( 3 ). Tropism and pathogenesis depend on exploitation of host factors supporting infection and evasion of cellular antiviral mechanisms ( 4 , 5 ). HCV naturally infects only humans, preventing studies of progressive immunopathogenesis or preclinical testing of novel therapeutics in an immunocompetent animal model.…”
Section: Introductionmentioning
confidence: 99%